Case method to increase student participation and problem-solving skills in biochemistry subject lesson study integrated at Khairun University - Sundari Sundari; Suparman Suparman; Abu Mas'ud; Said Hasan; Nurhasanah Nurhasanah; Nurmaya Papuangan; Dharmawaty M Taher; Yusmar Yusuf (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
The Biochemistry course is a basic and compulsory subject for Biology Education students. This study aims to determine students' level of participation and problem-solving skills through the ability to solve cases of Biomolecules and proteins on Student Worksheets (LKM). This is an Action Research integrated with lesson study with two cycles. The instruments used were student participation rubrics in the case method and LKM problem-solving skills in the Biochemistry course. The subjects in this study were 24 third-semester students of the Biology Education Study Program. Data analysis techniques through descriptive statistics with percentages. The results showed an increase in the percentage from cycle 1 to cycle 2. Student participation in collaborative activities increased from 71.5% to 73.3%, while problem-solving skills increased from 53.5% to 71.7%. Based on the observer transcripts, some students still do not understand the material and cases discussed in lectures in class and the laboratory. This is because students do not actively ask questions and do not have curiosity about the material and case explanations presented by lecturers or fellow students. This study shows that implementing the integrated case method in lesson study can increase student participation activities and problem-solving skills in Biochemistry courses.Abstrak Matakuliah Biokimia merupakan matakuliah dasar dan wajib bagi mahasiswa Pendidikan Biologi. Penelitian ini bertujuan untuk mengetahui tingkat partisipasi dan problem-solving skill mahasiswa melalui kemampuan menyelesaikan kasus-kasus konsep Biomolekul dan protein pada Lembar Kerja Mahasiswa (LKM). Ini adalah penelitian Action Reseach terintegrasi lesson study dengan dua siklus. Instrumen yang digunakan adalah rubrik pertisipasi mahasiswa dalam case method dan LKM problem-solving skill matakuliah Biokimia. Subjek dalam penelitian ini adalah 24 mahasiswa semester 3 prodi Pendidikan Biologi. Teknik analisis data melalui statistik deskriptif dengan persentase. Hasil penelitian menunjukkan peningkatan persentasi dari siklus 1 ke siklus 2. Aktivitas partisipasi mahasiswa dalam kolaborasi dari 71,5% menjadi 73,3%, sedangkan problem-solving skill mahasiswa dari 53,5% menjadi 71,7%. Berdasarkan transkrip observer masih ada mahasiswa yang kurang memahami materi dan kasus yang didiskusikan dalam perkuliahan di kelas maupun di laboratorium. Hal ini karena mahasiswa tidak aktif bertanya dan tidak memiliki rasa ingin tahu terhadap materi dan penjelasan kasus yang disampaikan oleh dosen atau sesama mahasiswa. Penelitian ini menunjukkan bahwa implementasi case method terintergrasi dalam lesson study dapat meningkatkan aktivitas partispasi dan problem-solving skill mahasiswa pada matakuliah Biokimia.